2017
DOI: 10.1186/s12879-017-2206-2
|View full text |Cite
|
Sign up to set email alerts
|

Norovirus infections in young children in Lusaka Province, Zambia: clinical characteristics and molecular epidemiology

Abstract: BackgroundThe burden, clinical features, and molecular epidemiology of norovirus infection in young children in southern Africa are not well defined.MethodsUsing data from a health facility-based surveillance study of children <5 years in Lusaka Province, Zambia presenting with diarrhea, we assessed the burden of norovirus infection. A convenience sample of 454 stool specimens was tested for norovirus using reverse-transcriptase polymerase chain reaction (RT-PCR). RT-PCR positive samples underwent additional n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
2
5
1
Order By: Relevance
“…Like the study of Zambia, in the current study, fever, diarrhea and vomiting were the most common complications in Norovirus-associated diseases. Nevertheless, there was no clear difference with Norovirus negative subjects in this regard [21]. Previous use of antibiotics and sex between two types of Norovirus infections and non-Norovirus infections did not show a significant difference in the present study.…”
Section: Discussioncontrasting
confidence: 74%
“…Like the study of Zambia, in the current study, fever, diarrhea and vomiting were the most common complications in Norovirus-associated diseases. Nevertheless, there was no clear difference with Norovirus negative subjects in this regard [21]. Previous use of antibiotics and sex between two types of Norovirus infections and non-Norovirus infections did not show a significant difference in the present study.…”
Section: Discussioncontrasting
confidence: 74%
“…The more sensitive PCR detection methods would no doubt pick up greater frequencies of rotavirus infections if applied to the same samples. As we previously showed [21], comorbidity is common in our environment and indeed our results here further reveal the multiplicity of enteric pathogens potentially contributing to disease. The question of the clinical relevance of isolated pathogens in diarrhoeal stools thus still remains important warranting further interrogation.…”
Section: Discussionmentioning
confidence: 50%
“…As expected, we found a predominance of norovirus GII (89.1%) compared to GI (10.9%). Several studies performed worldwide have demonstrated the same pattern of GII genotypes predominance among the norovirus infections, with GII detection rates varying between 72.1% and 94.9% [ 38 , 39 , 40 ]. In Latin American, studies performed in Chile and Bolivia detected GII percentages of 85% and 97.8%, respectively, among patients with AGE [ 6 , 41 ].…”
Section: Discussionmentioning
confidence: 97%